PERTUMBUHAN DAN MUTU FISIK BIBIT KAYU KUKU (Pericopsis mooniana) PADA MEDIA TANAM TAILING PERTAMBANGAN EMAS RAKYAT DENGAN PEMBERIAN AMELIORAN - Rizal Adi Saputra; Meyla Riniarti (ULIN: Jurnal Hutan Tropis, 2020)
One of the strategies in rehabilitation of gold mining tailings is used pioneer trees. Pericopsis mooniana is one of pioneer types which capable to adapt to marginal and unproductivel lands. The objective of this research were to find out the growth and physical quality of P. mooniana seedling on artisanal gold mining tailings with the addition of compost elephant dung and humic acid. Growth observation and physical quality assessment were done to P. mooniana seedlings aged 3 months and 10 days, placed on polybag (15/7.5 cm x 20 cm). The experimental design used a completely randomized design with six growth media as treatments and five replications, (1) topsoil 100%, (2) talings 100%, (3) tailings 50% + elephant dungs 50%, (4) tailings 50% + elephant dungs 50% + humic acid (2,000 ppm), (5) tailings 75% + elephant dungs 25%,(6) tailings 75% + elephant dungs 25% + (humic acid (2,000 ppm).  Data were analyzed statistically using analysis of variance followed with a Least Significant Difference test. The stages of the research were: seedling activity, growth observations and physical quality assessment seedlings. The parameter observed were percentage of life, increment height and diameter, number of leaf, leaf area, number of nodules, total dry weight, robustness, ratio of leaves and roots, and seed quality index. The result showed that P. mooniana seedlings were able to grow and adapt to artisanal gold mining tailings with a seedlings quality indexs value of more than (0.09), but the addition of ameliorant did not have any impact yet.